The effect of sales tax holidays on household consumption patterns - Nathan Marwell; Leslie McGranahan (Federal Reserve Bank of Chicago, 2010)
Sales tax holidays (STHs) are the temporary suspension of state (and some local) sales taxes on selected retail items for a brief period of time. The policy has gained popularity in recent years, beginning in one state in 1997 and growing to twenty by 2008. Despite the increased frequency with which states use STHs, little research has been conducted to study how households respond to this temporary tax manipulation. Our paper offers the first household-level, microeconometric evaluation on the effect of STHs on household consumption patterns. We find that on STHs, households increase the number of clothing and shoes bought by over 49 percent and 45 percent, respectively, relative to what they buy on average. Further, we find that this increase in consumption is limited to children's apparel and that the wealthiest households and households consisting of married parents and young children have the largest, statistically significant response to STHs; for example, households with incomes over 70,000 increase the number of children's clothing items purchased by 136 percent, while households that consist of married parents and young children increase the amount spent on children's clothing and shoes by 117 percent and 295 percent, respectively.
Keywords: 330